1999
DOI: 10.1109/26.795809
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of constructions of irregular Gallager codes

Abstract: The low density parity check codes whose performance is closest to the Shannon limit are`Gallager codes' based on irregular graphs. We compare alternative methods for constructing these graphs and present two results. First, we nd a`super{Poisson' construction which gives a small improvement in empirical performance over a random construction. Second, whereas Gallager codes normally take N 2 time to encode, we investigate constructions of regular and irregular Gallager codes which allow more rapid encoding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(64 citation statements)
references
References 11 publications
1
61
0
2
Order By: Relevance
“…4 This paper appears to have been influential. First, the idea of using irregular codes was taken up and extended by other researchers (see, e.g., [14]). Second, the main "concentration theorem" of [10] was extended to a large class of channel models in a landmark paper by Richardson and Urbanke [22], which first appeared in 1998.…”
Section: Further Developmentsmentioning
confidence: 99%
“…4 This paper appears to have been influential. First, the idea of using irregular codes was taken up and extended by other researchers (see, e.g., [14]). Second, the main "concentration theorem" of [10] was extended to a large class of channel models in a landmark paper by Richardson and Urbanke [22], which first appeared in 1998.…”
Section: Further Developmentsmentioning
confidence: 99%
“…However, in both cases, the performance exhibited by the resultant codes based on cascaded graphs appeared to be inferior to that of standard LDPC codes 4 since clearly, the block length of each stage of the cascaded code is lower than that of the overall length of the standard LDPC code. MacKay et al in [80] suggested that the parity-check matrix must be constrained to be in an approximate lower triangular (ALT) form depicted in Figure 4 which guarantees a linear increase of the encoding complexity. Richardson and Urbanke in [81] proved that in general, the encoding complexity increases nearly linear with the block length, being quadratic only in a small term g 2 , where g is referred to as the gap [82], which is a measure of the 'distance' [82] between the PCM and the lower triangular matrix as shown in Figure 4.…”
Section: A Encoding Of Low-density Parity-check Codesmentioning
confidence: 99%
“…Encoder complexity of LDPC codes is proportional with the square of code length (n 2 ), therefore, encoding process time is longer than turbo encoding. In construction of LDPC codes, choosing appropriate upper triangle parity check matrix, provides significant encoding complexity reduction as in References [7,8]. These kind of matrix transformations may converse the sparsity of the original matrix, but do not affect code performance.…”
Section: Introductionmentioning
confidence: 98%